2009
DOI: 10.1002/mabi.200800355
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Star Adhesive Sealants Based On PEG/Dextran Hydrogels

Abstract: Swellable PEG amine/dextran aldehyde composite materials are emerging as a controlled, biocompatible tissue adhesive. We explain how preservation of natural tissue amines provides biocompatibility for PEG/dextran that exceeds the stringent, destructive cyanide-based chemistry of cyanoacrylates, and adhere far better than fibrin glue. Strategic variations of material composition allow for the improvement of biocompatibility and adhesion strength. Material variations can be tailored to match the needs of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…[15] Dermabond 1 in contrast, is a much stronger adhesive, [16] and in glueing chamois leather we found high adhesive strength values of approximately 0.4 MPa. The adhesive bond strength of the TMPE-TMC based networks was found to be even better than that of Dermabond 1 .…”
mentioning
confidence: 77%
“…[15] Dermabond 1 in contrast, is a much stronger adhesive, [16] and in glueing chamois leather we found high adhesive strength values of approximately 0.4 MPa. The adhesive bond strength of the TMPE-TMC based networks was found to be even better than that of Dermabond 1 .…”
mentioning
confidence: 77%
“…Cytotoxicity and proliferation of 3T3 rat fi broblast tests revealed that PEG/dextran was signifi cantly less cytotoxic than octyl cyanoacrylate. The highermolecular-weight dextran aldehyde exhibited lower cytotoxicity as well as higher proliferation [ 95 ] .…”
Section: Peg-based Sealantmentioning
confidence: 98%
“…PEG/dextran aldehyde was developed as biocompatible tissue adhesive [ 95 ] . It consisted of a relatively short-chain PEG polymer (linear PEG of 2 kDa or 8-arm PEG of 10 kDa) containing amine-terminated groups and dextran-containing aldehyde groups.…”
Section: Peg-based Sealantmentioning
confidence: 99%
“…PEG replete with amine groups and oxidized dextran react at body temperature in a Schiff base reaction to form adhesive materials as aldehydes bind to tissue amines. The reaction is reversible and the material hydrolyzes to its polymeric components 16,17 . Although PEG polymers may undergo enzymatic degradation, significant fluid uptake and swelling dominate the degradation of our formulated PEG:dextran hydrogels, resulting in hydrolyticsensitive materials.…”
Section: Hhs Public Accessmentioning
confidence: 99%